In Praise of Memory (Journal of Parents and Teachers, 2025)
The author analyzes the criticisms of the use of memory and memorization in schools, often seen as antagonistic to meaningful learning. She highlights the value and effectiveness of selective memorization activities to promote secure, functional, and meaningful learning, and proposes various effective activities and strategies for the development of different types of memory.
Keywords: memory; memorization; meaningful learning; critical thinking; autonomous learning